Multifunctional Paper-Based Analytical Device for In Situ Cultivation and Screening of Escherichia coli Infections - Noiphung, Julaluk (Sci Rep, 2019)
Point-of-care testing (POCT) for uropathogen detection and chemical screening has great benefits for the diagnosis of urinary tract infections (UTIs). The goal of this study was to develop a portable and inexpensive paper-based analytical device (PAD) for cultivating bacteria in situ and rapidly testing for nitrite on the same device. The PAD was fabricated using a wax printing technique to create a pattern on Whatman No. 1 filter paper, which was then combined with a cotton sheet to support bacterial growth. Nitrite detection was based on the principle of the Griess reaction, and a linear detection range of 0–1.6 mg/dL (R(2) = 0.989) was obtained. Scanning electron microscopy (SEM) analysis demonstrated that the bacteria were able to grow and formed a cluster on the cellulose fibres within 2 hours. The enzyme β-glucuronidase, which is specifically produced by Escherichia coli, was able to convert the pre-immobilized 5-bromo-4-chloro-3-indolyl-β-D-glucuronide sodium salt (X-GlcA), a colourless substrate, generating a blue colour. Under optimum conditions, the proposed device allowed bacterial concentrations in the range of 10(4)–10(7) colony forming units (CFU)/mL to be quantified within 6 hours. Moreover, the use of this device enables the identification of E. coli pathogens with selectivity in real urine samples. In conclusion, the PAD developed in this study for UTI screening provides a rapid, cost-effective diagnostic method for use in remote areas.